Efficacy of bio-rational insecticide for eco-friendly management of pod borer of mung bean - Tanzum, N; Miah, MRU; Ahiduzzaman, M; Khandakar, MS; Hossain, MS (Annals of Bangladesh Agriculture, 2024)
Pod borer species Maruca vitrata (Geyer) and Euchrysops cnejus (Fab.) are the major limiting constraints in mung bean. The present experiment was conducted in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during March to June 2021 to develop an ecofriendly management approach against pod borer attacking mung bean. Four eco-friendly biopesticides (Biomax 1.8 EC (Abamectin) @ 1.2 ml/L, Tracer 45 SC (Spinosad) @ 0.4 g/, Fytomax PM (0.1% Azadirachtin) @ 5.0 ml/L, Neem Seed kernel Extract (NSKE) @ 50.0 g/L) and clean cultivation were tested against pod borers of mung bean variety BU mug 4. An untreated control treatment was maintained for comparison. The marginal benefit-cost ratio of the treatments and the impact of the treatments on the abundance of beneficial arthropods in the experimental plots were recorded. The management approaches did not affect the abundance of beneficial arthropods in the bean field. The findings revealed that the lowest rate of pod infestation (1.9% by n/n and w/w) as well as the highest marketable yield (1.55 MT/ha) and marginal benefit- cost ratio (3.02) were obtained with the foliar spray with Tracer 45 SC (Spinosad) @0.4 g/L of water at 15 days interval. Tracer 45 SC (Spinosad) @ 0.4 g/L of water at 15 day intervals is an effective, suitable, and viable approach for suppressing pod borer complex without harm to beneficial arthropods in the mung bean field. Ann. Bangladesh Agric. (2023) 27 (1): 71-79